Collaboration in Higher Education - Abegglen, Sandra; Burns, Tom; Sinfield, Sandra (Bloomsbury Academic, 2023)
Collaboration in Higher Education, an open access book, focuses on the opportunities and challenges created by engaging in collaboration and partnership in higher education. As higher education institutions become ever more competitive to sustain their place in a global, neoliberal education market, students and staff are confronted with alienating practices. Such practices create an individualistic, audit and surveillance culture that is exacerbated by the recent COVID-19 pandemic and the wholesale 'pivot' to online teaching. In this atomised and competitive climate, this volume synthesises theoretical perspectives and current practice to present case study examples that advocate for a more inclusive, cooperative, collaborative, compassionate and empowering education, one that sees learning and teaching as a practice that enables personal, collective and societal growth. The human element of education is at the core of this book, focusing on what we can do and achieve together: students, academic staff, higher education institutions and relevant stakeholders. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.